2006
DOI: 10.1002/pmic.200600499
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of glutathione transferases from the liver fluke parasite,Fasciola hepatica

Abstract: The parasite Fasciola hepatica causes major global disease of livestock, with increasing reports of human infection. Vaccine candidates with varying protection rates have been identified by pre-genomic approaches. As many candidates are part of protein superfamilies, sub-proteomics offers new possibilities to systematically reveal the relative importance of individual family proteins to vaccine formulations within populations. The superfamily glutathione transferase (GST) from liver fluke has phase II detoxifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 37 publications
6
82
1
1
Order By: Relevance
“…However, as is shown in Figures 1D and 1E, secretion of 28 kDa Cs28σGST3 species appeared to be substantially decreased (up to 95%) in the bile stimulated ESP, while that of immunologically-related high-molecular weight proteins were profoundly augmented as bile concentrations increased. This is a unique finding observed for the first time with C. sinensis ESP, but not with other trematode such as F. hepatica and O. viverrini , which also reside in the mammalian bile duct [13], [16], [34]. We purified the global CsGST fractions using GSH-matrix and observed that the 85 kDa protein shared peptide fragments with the 28 kDa Cs28σGST3, thus representing a genuine Cs28σGST3.…”
Section: Discussionmentioning
confidence: 70%
“…However, as is shown in Figures 1D and 1E, secretion of 28 kDa Cs28σGST3 species appeared to be substantially decreased (up to 95%) in the bile stimulated ESP, while that of immunologically-related high-molecular weight proteins were profoundly augmented as bile concentrations increased. This is a unique finding observed for the first time with C. sinensis ESP, but not with other trematode such as F. hepatica and O. viverrini , which also reside in the mammalian bile duct [13], [16], [34]. We purified the global CsGST fractions using GSH-matrix and observed that the 85 kDa protein shared peptide fragments with the 28 kDa Cs28σGST3, thus representing a genuine Cs28σGST3.…”
Section: Discussionmentioning
confidence: 70%
“…At least seven speciesindependent classes of cytosolic GST are known and may be distinguished from each other on the basis of substrate specificity and inhibitor sensitivity (45,47). Three GST classes, representing at least six distinct enzymes, have been identified in F. hepatica (10,45). We have not determined if enzyme activity is important for the activation of DCs described here.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…A limited understanding of the Cat L protease sub-proteome may be hindering development of this vaccine candidate protein family [25]. A key consideration for vaccine development is to target functional components that are required for the survival of the parasite [26].…”
Section: Introductionmentioning
confidence: 99%